2021
DOI: 10.3168/jds.2020-19609
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: The welfare of dairy cattle housed in tiestalls compared to less-restrictive housing types: A systematic review

Abstract: Many dairy cattle worldwide are housed in tiestalls, meaning that they are tethered by the neck to individual stalls. On some farms, tied cattle are permitted seasonal access to pasture, but otherwise their movements are restricted compared with cows housed in freestall barns or other loose housing systems. The aim of this systematic review is to summarize the scientific literature pertaining the welfare of tied dairy cattle through comparison with less-restrictive housing systems. Articles identified by PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 139 publications
(244 reference statements)
1
35
0
Order By: Relevance
“…The major effect of this under-recognition of lameness is not that lame cows are not treated but that treatment is delayed more than 3 weeks, especially of less severely lame cows [ 105 ]. Lameness prevalence ranges from 5.1% to 54.8% [ 106 ], with the highest rates observed in herds housed in tie-stalls [ 107 ] and free-stalls [ 108 , 109 , 110 ]. Although the effect between free-stall and tie-stall housing on lameness incidences is not clear [ 107 ], several studies conclude that lameness in tie-stalls system are underestimated due to the difficulty of assessing it [ 111 , 112 ].…”
Section: Pain Associated With Lamenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The major effect of this under-recognition of lameness is not that lame cows are not treated but that treatment is delayed more than 3 weeks, especially of less severely lame cows [ 105 ]. Lameness prevalence ranges from 5.1% to 54.8% [ 106 ], with the highest rates observed in herds housed in tie-stalls [ 107 ] and free-stalls [ 108 , 109 , 110 ]. Although the effect between free-stall and tie-stall housing on lameness incidences is not clear [ 107 ], several studies conclude that lameness in tie-stalls system are underestimated due to the difficulty of assessing it [ 111 , 112 ].…”
Section: Pain Associated With Lamenessmentioning
confidence: 99%
“…Lameness prevalence ranges from 5.1% to 54.8% [ 106 ], with the highest rates observed in herds housed in tie-stalls [ 107 ] and free-stalls [ 108 , 109 , 110 ]. Although the effect between free-stall and tie-stall housing on lameness incidences is not clear [ 107 ], several studies conclude that lameness in tie-stalls system are underestimated due to the difficulty of assessing it [ 111 , 112 ]. The use of a Lameness Scoring System (LCS) on a regular basis is the most effective means of identifying lameness in cows.…”
Section: Pain Associated With Lamenessmentioning
confidence: 99%
“…A review of the literature comparing the effects of tie-stall and free-stall housing systems on the performance, health, fertility and behavior of dairy cows revealed that each system has its strengths and weaknesses, but the analyzed parameters tended to be higher in free-stall barns [9]. It is difficult to accept the lack of basic freedom of movement in tie-stall systems [10,11]. Research has shown that selected technological solutions can improve animal welfare and decrease greenhouse or toxic gas emissions and microbiological contamination in buildings, which indirectly improves the health status and disease resistance of animals [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This housing system is controversial because it restricts the voluntary movement of the cows and their ensuing social behavior [3,4]. Moreover, tie-stalls are associated with problems including hock swellings and abrasions, neck lesions, broken tails, and lameness [5][6][7]. Consequently, for lactating cows any exercising opportunities as often as possible have become mandatory and an integral part of the Dairy Cattle Code of Practice of the National Farm Animal Care Council [8].…”
Section: Introductionmentioning
confidence: 99%